2017
DOI: 10.1038/s41598-017-07147-2
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater nitrate response to sustainable nitrogen management

Abstract: Throughout the world, nitrogen (N) losses from intensive agricultural production may end up as undesirably high concentrations of nitrate in groundwater with a long-term impact on groundwater quality. This has human and environmental health consequences, due to the use of groundwater as a drinking water resource, and causes eutrophication of groundwater-dependent ecosystems such as wetlands, rivers and near-coastal areas. At national scale, the measured nitrate concentrations and trends in Danish oxic groundwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(113 citation statements)
references
References 45 publications
2
108
0
3
Order By: Relevance
“…Eutrophication risk is defined by nitrogen application in coastal watersheds that exceeds 10 kg ha −1 and coastal groundwater discharge that exceeds 100 m 2 a −1 . The threshold value for nitrogen input corresponds to values that have historically led to strongly elevated nitrogen concentrations in groundwater in Europe and North America 39,40 that have contributed to the eutrophication of terrestrial and nearshore ecosystems 41 . Note that the lack of data outside of North America and Europe make the extrapolation uncertain, and the numbers reported here should be considered a first order estimate.…”
Section: Resultsmentioning
confidence: 99%
“…Eutrophication risk is defined by nitrogen application in coastal watersheds that exceeds 10 kg ha −1 and coastal groundwater discharge that exceeds 100 m 2 a −1 . The threshold value for nitrogen input corresponds to values that have historically led to strongly elevated nitrogen concentrations in groundwater in Europe and North America 39,40 that have contributed to the eutrophication of terrestrial and nearshore ecosystems 41 . Note that the lack of data outside of North America and Europe make the extrapolation uncertain, and the numbers reported here should be considered a first order estimate.…”
Section: Resultsmentioning
confidence: 99%
“…Hansen et al [12] found significant correspondence between developments in N surplus and nitrate concentrations in upper groundwater for four subsequent development periods for Danish agriculture in the period 1946-2012, and similarly for developments in the nitrogen use efficiency.…”
Section: Nitrogen Budgets and Relation To Water Qualitymentioning
confidence: 96%
“…The production of biomass in each scenario is based on an extensive set of agricultural statistics on crop productivity and land use that have been used to estimate the productivity of all relevant crops for 2020 [7,10]. The basis for these estimates is, in line with previous studies of decadal trends in Danish agriculture [7,11], a linear extrapolation of present crop productivity as well as literature values when accurate statistics were not available. Underlying model assumptions and data references are further explained in the supplementary information.…”
Section: Methodsmentioning
confidence: 99%